Querida amiga Marta: sexualidade, feminismo e poder no programa TV Mulher - Bueno, Heitor Campos (2015)
This work has as main thematic approach to analyze the effects produced in the viewer public by discourses present in the "Comportamento Sexual" presented by psychologist Marta Suplicy (1945 -) on TV Mulher program. Therefore, we use as documentary sources reports contained in correspondence sent to the program between the years 1980 and 1982 as well as four of Marta Suplicy publications: Conversando sobre Sexo (1983), Condição da Mulher Amor, Paixão, Sexualidade (1984), De Mariazinha a Maria (1985), Reflexões Sobre o Cotidiano (1986). As complementary and not a priority source we will also bring the reports in an interview granted by psychologist Marta Suplicy. From the discussions about power and sexuality proposed by the French philosopher Michel Foucault we shall ponder the speeches presented by Marta Suplicy, about sexuality and social status of women, point to a dichotomous relation to regulation and liberalization. In order to bring better analytics on the subject and the period in question, the research discuss issues that concern the Brazilian print and broadcast media products focusing on the so-called women's press and women's and feminist movements operating in Brazil